Authenticity and Walkability of Iconic Heritage Destination Bandung Indonesia - Yadi; Hariyadi Triwahyu Putra (International Journal Of Community Service, 2021)
This study aims to examine the effect of authenticity and walkability on revisit intention mediated by tourist satisfaction. These four variables are measured using a number of statements on a Likert scale which are confirmed to have completed the validity and reliability tests. Data were collected using a questionnaire which was distributed to 271 respondents based on convenience sampling. Furthermore, the data were obtained and analyzed using structural equation modeling (SEM) and the Sobel test as a basis for hypothesis testing. The results of the hypothesis test explain the rejection of the null hypothesis, which means that there is support for empirical data on the proposed research hypothesis. This illustrates that authenticity and walkability directly affect tourist satisfaction positively and significantly. Meanwhile, revisit intention is influenced positively and significantly both directly by authenticity and walkability and indirectly through tourist satisfaction. Thus, all attributes of authenticity and walkability have a very important role in fulfilling tourists' expectations when appreciating historical buildings in a heritage tourism area. The authenticity attributes of historical buildings that need the attention of relevant stakeholders are historical value, authenticity, originality, and maintenance. Some of the critical elements of walkability that also need to be maintained such as security, comfort, accessibility, connections with other destinations, and pedestrian friendliness for pedestrians.